Automation in the pharmaceutical analysis laboratory: a centralized/decentralized approach - Scypinski, Stephen (Hindawi Publishing Corporation, 1995)
It has been over 10 years since robots have appeared in the pharmaceutical analysis laboratory. In the early days, it was common for one selected individual to be responsible for the programming, usage and maintenance of the robots(s). However, the increasing use of robotics has prompted the formation of robotics ‘laboratories’ and/or ‘groups’. This is especially true when multiple robotic systems and applications are involved. Over the past several years at ISLAR, many champions of robotics have given presentations on the setup and usage of robotics within their organizations. These managers have described both the ‘centralized’ and ‘decentralized’ approaches to the implementation of robotics. In the centralized system, a single group is charged with all aspects of the robotic project, including justification, purchase, validation, use and maintenance. Under such an arrangement, samples are usually given to the robotics group for analysis. In contrast, a totally decentralized approach to robotics would have units interspersed throughout the organization, with each individual group responsible for their respective unit(s), in much the same way as liquid chromatographs are considered. At Hoffmann-La Roche, aspects of both the centralized and decentralized approaches to robotics are used which make our combined system the ‘best of both worlds’. This paper describes the Roche philosophy towards robotics and highlights the advantages to the system used.